Omecamtiv Mecarbil in the treatment of heart failure: the past, the present, and the future - Zhou, Shujing; Liu, Ying; Huang, Xufeng; Wu, Chuhan; Pórszász, Róbert (Frontiers in Cardiovascular Medicine, 2024)
Heart failure, a prevailing global health issue, imposes a substantial burden on both healthcare systems and patients worldwide. With an escalating prevalence of heart failure, prolonged survival rates, and an aging demographic, an increasing number of individuals are progressing to more advanced phases of this incapacitating ailment. Against this backdrop, the quest for pharmacological agents capable of addressing the diverse subtypes of heart failure becomes a paramount pursuit. From this viewpoint, the present article focuses on Omecamtiv Mecarbil (OM), an emerging chemical compound said to exert inotropic effects without altering calcium homeostasis. For the first time, as a review, the present article uniquely started from the very basic pathophysiology of heart failure, its classification, and the strategies underpinning drug design, to on-going debates of OM's underlying mechanism of action and the latest large-scale clinical trials. Furthermore, we not only saw the advantages of OM, but also exhaustively summarized the concerns in sense of its effects. These of no doubt make the present article the most systemic and informative one among the existing literature. Overall, by offering new mechanistic insights and therapeutic possibilities, OM has carved a significant niche in the treatment of heart failure, making it a compelling subject of study.